Sequencing synthetic copolymers using electrospray ionization mass spectrometry - Giguere, Marie-Soleil (University of Ottawa (Canada), 2003)
The dissociation of gas-phase synthetic homopolymers poly(butyl acrylate) (PBA), poly(methyl methacrylate) (PMMA) and poly(vinyl acetate) (PVAc) ionized by Li+ or Na+ was investigated by electrospray-ionization tandem mass spectrometry. Based on these results it was possible to use tandem mass spectrometry to sequence three copolymers produced by free radical polymerization (PBA/PVAc, PBA/PMMA and PMMA/PVAc). In the case of PVAc containing copolymers, tandem mass spectrometry yielded partial sequence information including the number of VAc monomers and consecutive BA or MMA monomers while the complete sequence (and mixture of sequences) could be deduced for PBA/PMMA. The poly(vinyl acetate) ions lose acetic acid molecules from the polymer side chain, and ultimately metal acetate, to form a polyene with a positive charge on the carbon backbone while PBA and PMMA fragment along the polymer backbone. An extensive study was made of the dissociation characteristic of PVAc. Collision-induced dissociation (CID) was performed at different center-of-mass collision energies to study the sequential appearance of the fragment ions. Molecular mechanics/molecular dynamics (MM/MD), Hartree-Fock, semi-empirical and density functional calculations were employed to model the lowest energy dissociation processes.
Keywords: Chemistry, Analytical.; Chemistry, Polymer.